Global resource sharing - Frederiksen, Linda; Bean, Margaret; Nance, Heidim; Ohio Library and Information Network (Oxford, United Kingdom Chandos Publishing, 2012)
Written from a global perspective, this book reviews sharing of library resources on a global scale. With expanded discovery tools and massive digitization projects, the rich and extensive holdings of the world's libraries are more visible now than at any time in the past. Advanced communication and transmission technologies, along with improved international standards, present a means for the sharing of library resources around the globe. Despite these significant improvements, a number of challenges remain. Global Resource Sharing provides librarians and library managers with a comprehensive background in and summary of the issues involved in global resource sharing. Analyses current and future environments for international resource sharing, including past research and discussionsProvides an international perspective on a global library issueIncludes examples of successful and innovative global resource sharing initiatives.
Keywords: Interlibrary loans -- International cooperation -- Case studies; Interlibrary loans -- International cooperation; International librarianship; Library cooperation -- Case studies; Library cooperation